Post - cracking behavior of the tensile specimens made from Ultra high performance concrete, reinforced by GFRP rebar - hossein ali rahdar; M. Ghalehnovi (Journal of Structural and Construction Engineering, 2019)
Since it is very important to know the material's behavior to evaluate the nonlinear behavior of structures, it is necessary to know the tension stiffening phenomenon and its effect on the behavior of the reinforced concrete members to examine their behavior in tension. For a reinforced concrete member, the reinforcement confined concrete affects the member's behavior after being cracked in the spacing between two cracks, and the reinforcement rebar in the concrete member shows less strain than the bare rebar. This affects the width of cracks and the stiffness of the member under tension. In this research the experimental method is used to tensile behavior of concrete members reinforced by GFRP rebar therefore the effect of rebar type, reinforcement ratio and c/d ratio on the cracking behavior of ultra high performance concrete (UHPC) is evaluated.The results show that increasing the rebar cover to diameter ratio of all specimens, their initial stiffening increases before the cracking stage in concrete. Also, the tension stiffening effect does not change as the type of the rebar changes. Finally, the spacing of cracks, the way they are distributed and their behavior are discussed.Keywords:Ultra High performance concrete, tensile strengthGFRP rebar,Tensile member. Cracking